Efficient adenoviral-mediated ornithine transcarbamylase expression in deficient mouse and human hepatocytes. - Morsy, M A (1993)
100% of primary human hepatocytes infected with an adenoviral vector carrying beta-galactosidase expressed the exogenous gene. Expression was also achieved in > 40% of adult mouse hepatocytes in vivo. Normal levels of activity were achieved in mouse ornithine transcarbamylase (OTC)-deficient primary hepatocytes using another adenoviral vector carrying human OTC cDNA. Study of OTC-deficient primary human hepatocytes from a single patient confirmed the utility of adenoviral delivery of OTC. We describe adenoviral-mediated exogenous gene expression in human and mouse hepatocytes in vitro and in mouse liver in vivo. Data suggest that adenoviral vectors may be useful for correcting OTC deficiency.